Case Report: Recovery of consciousness ahead of MRI image lesion information in cerebral fat embolism syndrome - Zhuang, Zhixiong; Bo, Yan; Pan, Yunpin; Huang, Jianfeng (Frontiers in Medicine, 2025)
BackgroundThe absence of definitive international guidelines for the diagnosis and treatment of fat embolism syndrome (FES) has prompted clinicians to undertake independent research. The admission of a patient with suspected cerebral FES (CFES) prompted clinicians to engage in self-directed learning.Case summaryWe presented a case of a 28-year-old male patient who had developed CFES as a complication of a fracture. The initial magnetic resonance imaging (MRI) scan revealed the presence of scattered, multiple punctate lesions in the majority of the cerebral white matter. Following a series of treatments, including supportive care, the final MRI scan (on the fifth day) demonstrated that the majority of lesions had either been resorbed or were undergoing resorption, with a small number of lesions demonstrating fusion and an increase in size. However, the patient’s impaired consciousness was successfully restored 5 days after the onset of the disease.ConclusionMRI findings should serve as the foundation for diagnosing CFES, rather than being used as a criterion for evaluating discharge. We proposed that MRI findings of “star pattern” and “vasogenic edema” represented the optimal imaging criteria for diagnosing CFES. The timing of the diagnosis of CFES can be utilized as a validation measure for the diagnosis of CFES, which was conducive to the early and complete recovery from consciousness disorders. Moreover, we found the lesion information from MRI images lags behind the rate of recovery in the level of consciousness. The clinician can consider that the cerebral fat embolism syndrome has reached the therapeutic expectation when the patient’s level of consciousness is restored. The patient can then be asked to be followed up after discharge from the hospital, and the end point of the follow-up period can be indicated by observing the complete disappearance of the lesion information shown on MRI.